A Biosurfactant‐Inspired Heptapeptide with Improved Specificity to Kill MRSA. Issue 6 (11th January 2017) - Liu, Yuan; Ding, Shuangyang; Dietrich, Richard; Märtlbauer, Erwin; Zhu, Kui
Abstract: The emergence and rapid spread of methicillin‐resistant Staphylococcus aureus (MRSA) poses a serious threat to public health. New antibiotics and strategies are urgently needed to combat S. aureus associated infections. Bacaucin, a novel cyclic lipopeptide from Bacillus subtilis CAU21, is reported. Bacaucin shows broad antibacterial activity against Gram‐positive bacteria, but is also hemolytic and cytotoxic. However, bacaucin‐1, a bacaucin‐inspired ring‐opened heptapeptide, shows specific antibacterial activity against MRSA by a membrane‐disruptive mechanism without detectable toxicity to mammalian cells or induction of bacterial resistance. Bacaucin‐1 was efficient in preventing infections in both in vitro and in vivo models and is a valuable prototype antibiotic with high potential against S. aureus infections. Abstract : Pandora's box with hope : A natural cytotoxic antibiotic bacaucin (see picture; red), a cyclic lipopeptide from Bacillus subtilis, is presented. The safe bacaucin‐inspired synthetic derivative bacaucin‐1 (blue) shows specific antibacterial activity against methicillin‐resistant Staphylococcus aureus (MRSA), and is efficient in preventing infections in vitro and in vivo.